EASTERN ARCTIC ICE SEASONAL OUTLOOK 1970. - NAVAL OCEANOGRAPHIC OFFICE WASHINGTON D C (1970)
Forecast trends for five major eastern Arctic ports resupplied by the Military Sea Transportation Service (MSTS) are listed in table 1. The normal escorted and unescorted entry date for each port is shown with the predicted trend. In addition, a written and graphic description of expected ice conditions is presented for Baffin Bay, Davis Strait, and the Labrador and east Greenland coasts between mid-May and mid-August. Monthly prognostic ice charts for this period include envelopes showing the maximum and minimum pack edges for each month. (Author)